The Value of Rubbish in Francophone Chinese Art Installations - Rosalind Silvester (Modern Languages Open)
This article investigates the presentation and function of rubbish in transcultural installation art and rethinks the aesthetic value of waste in the broad context of two contemporary theories of cultural production – the anthropology of waste and the cultural history of waste. It explores the possibilities that this art offers for new ways of perceiving and understanding waste that appeal both to our imagination and ecological consciousness. Rubbish, considered before the late nineteenth century as being outside of, even opposed to, culture proper, is reconceptualized in contemporary society, giving rise to a new, less negative, though no less complex, relationship between waste and culture. We focus on displays created by Chen Zhen, Wang Du and Shen Yuan, francophone Chinese artists who, by means of the practices of recuperation and recycling, raise awareness of social, political and environmental issues, leading to the viewer’s cultural engagement in a trajectory of change. In giving voice to a vision, their works enable an analysis of the cultural transformation of both subject (artist/viewer) and object (primary material) brought about by the ubiquitous presence of rubbish as physical and discursive reality.